Structure, electronic properties and electron energy loss spectra of transition metal nitride films - Matenoglou, G. M.; Patsalas, Panos; Koutsokeras, Loukas E. (My University, 2013)
We present a thorough and critical study of the electronic properties of the mononitrides of the group IV-V-VI metals (TiN, ZrN, HfN, NbN, TaN, MoN, and WN) grown by Pulsed Laser Deposition (PLD). The microstructure and density of the films have been studied by X-Ray Diffraction (XRD) and Reflectivity (XRR), while their optical properties were investigated by spectral reflectivity at vertical incidence and in-situ reflection electron energy loss spectroscopy (R-EELS). We report the R-EELS spectra for all the binary TMN and we identify their features (metal-d plasmon and N-p + metal-d loss) based on previous ab-initio band structure calculations. The spectral positions of p + d loss peak are rationally grouped according to the electron configuration (i.e. of the respective quantum numbers) of the constituent metal. The assigned and reported R-EELS spectra can be used as a reference database for the colloquial in-situ surface analysis performed in most laboratories
Keywords: Materials science; Nitrides; Microstructure; Transition metal nitrides; Titanium nitride; Transition metals